REFLECTIONS ABOUT FORMATION OF TEACHERS IN PHYSICAL EDUCATION (Fiep Bulletin - online, 2014)
This study indicates possibilities to think on the educators' formation and physical education teachers. The research is already part of the master's degree dissertation in conclusion phase. The objective is to present experiences and anguishes that we have during our professional life, in the ambit of the academic formation, in the discussions in the universities with the teachers and academic, seeking authors that discuss the subject, for best could understand it. It presents a revision of literature triangulando with the interviews done with Leisure's teachers and Recreation of the 3 State Universities of Paraná. Being: State University of the West of Paraná (UNIOESTE) State University of Ponta Grossa (UEPG) and State University of Maringá (UEM). You analyzes a to think on the physical education degrees, allowing to find questionamentos, challenges, experiences and proposed that contribute in the attempt of overcoming the crisis in that meet.
Keywords: professional formation; human formation; physical education